Impact of the exotic parasitoid Epidinocarsis lopezi on cassava mealybug (Phenacoccus manihoti) populations - Hammond, W.N.O.; Neuenschwander, Peter; Herren, H.R. (Springer, 1987)
Epidinocarsis lopezi an exotic parasitoid to Africa, was first released to control the cassava mealybug (CM), Phenacoccus manihoti, at IITA (Ibadan) in November 1981, and a year later at Abeokuta, both in southwestern Nigeria. Population dynamics study of CM and its natural enemies was conducted for 4 years. CM population peaks usually occurred during the second half of the dry season (January-April). E. lopezi was the only natural enemy that was found during the whole year and in high densities. Parasitization rates of E. lopezi alternated with CM densities, thus suggesting a regulatory effect on CM populations by this parasitoid. CM populations were drastically reduced in release fields when compared with control fields. Subsequently CM populations have been maintained below injury levels for 4 years. E. lopezi is considered an efficient parasitoid of the CM.